PELAYANAN KAPAL DAN BARANG DI PELABUHAN CILACAP - Bambang Sudjasta (Bina Teknika, 2016)
position is strategic to support marine transportation system, where westward the island of Sumatera, South Asia, and the Middle East, to the east is Nusatenggara, and until the Australian continent. Cilacap port has a support area (hinterland) potential, namely the southern part of Central Java, Yogyakarta and West Java southeast. Increased support the region's economy will lead to increased trade that will improve the flow of goods/ commodities and the number of ship visits in the port of Cilacap. The number of ship visits dominated by tankers, and commodities trading is dominated by fuel oil. This study aims to conduct a review of port services, especially services to ships and service of loading and unloading of goods that must be continuously improved quality and quantity.